THE IMPACT OF LOCUS CONTROL AS A MEDIATOR ON JOB SATISFACTION IN XYZ'S NON-FRANCHISE BUSINESS - Yustinus Yuniarto; Michael Christian; Celia Paramitha (Universitas Pelita Harapan, 2022)
The phenomenon that the work environment and personal aspects of workers, such as work discipline and locus control, should go hand in hand to achieve the expected job satisfaction motivates this research. The purpose of this research is to identify and explain the factors that influence locus control and job satisfaction. Also, to identify and explain the role of locus control as a moderator between non-physical work environment and work discipline on job satisfaction. This quantitative study involves 30 employees from XYZ's non-franchise business in Jakarta and employs a structural model with SmartPLS as an analytical tool. A questionnaire instrument was used in this study's survey. According to the findings of this study, the work environment has a small impact on locus control and job satisfaction. Meanwhile, work discipline affects locus control but not job satisfaction. This finding supports another finding that employees' locus of control at work influences job satisfaction. In the indirect effect, locus control does not serve as a moderator between work environment and job satisfaction or between work discipline and job satisfaction.